Pentingnya Komunikasi Interpersonal Pembina Dalam Meningkatkan Partisipasi Siswa Mengikuti Kegiatan Ekstrakurikuler - MHD Natsir; Rahman, Adinda Fitria (Universitas Negeri Padang, 2024)
The purpose of this study is to explain the importance of interpersonal communication of instructors in increasing student participation in extracurricular activities. This study utilizes data from literature, with books as the main reference for the information needed. This study was conducted through reading, reviewing, and analyzing various documents, including books, articles, and other scientific works. The results of this study found that: 1.) Openness, instructors who have an open attitude will create a conducive environment and will make members have high participation in participating in extracurricular activities. 2.) Empathy, instructors who have an empathetic attitude will increase student participation in participating in extracurricular activities. 3.) Supportive attitude, support from instructors will make members participate more in participating in extracurricular activities. 4.) Positive attitude, instructors who have a positive attitude will make members participate more in participating in extracurricular activities. 5.) Equality attitude, instructors who have an equality attitude will increase member participation. Keywords: Interpersonal Communication, Student Participation, Extracurricular.